The Diversification Processes in Ensuring Sustainable Development of the Agrarian Sector of the Agro-Industrial Complex (AIC): Problems and Prospects of Transformation under the Current Conditions - Olga SMYSLOVA; Anastasia KOKOREVA; Anna IVANOVA; Natalia MOROZOVA; Natalia FILONENKO (Communications of International Proceedings, 2022)
The paper addresses the issues of the diversification approach application to ensuring the sustainable development of the agrarian sector of the Agro-Industrial Complex (here and after: the Agro-Industrial Complex- AIC). The relevance of the topic is conditioned by the growing interest in the resource potential enhancement in the agrarian sector of AIC. The survey is focused on the key indicators of the agricultural development enables to identify the problems that hinder the development of the Russian agricultural producers and to propose a model to diversify Russian agriculture into new types of activities based on the use of innovative, resource-saving technologies, the integrated use of land resources, production capacities and the entire resource potential of agribusinesses. At the same time, the model draws special attention to the specificity of available resources, their potential, natural and climatic conditions, consumer activity, as well as price categories of food produced. The research based on the application of both theoretical and empirical methods (analysis, synthesis, comparison, data collection and others) has made it possible to achieve its main goal- to work out those ways that can ensure the efficient and sustainable development of the agrarian sector of AIC with the help of the diversification approach.
Keywords: agrarian sector of AIC; resource potential of agribusinesses; sustainable development; diversification approach; rural areas